Probiotic Shelf-life, Mineral Contents and Others Properties of Probiotic Yoghurts Supplemented with Corn Flour - Filiz Yangılar; Songul Cakmakci (Journal of Agricultural Sciences)
It was aimed in the present study to determine the mineral content, probiotic, sensory, physical and chemical characteristics of probiotic yoghurt-PC (only probiotic Lactobacillus acidophilus DSMZ 20079 strains with direct vat set starter culture) obtained with the addition of organic corn flour (CF) at different concentrations during a 21-day storage period. It was found in the study that all probiotic yoghurt formulations with CF gave high L. acidophilus viabilities between 6.89 and 7.87 log cfu/g during the storage and CF addition did not affect the viability of the probiotic bacteria. The viscosity and dry matter content increased in CF added samples with increasing CF concentrations. Syneresis in PC yogurt sample was found to be significantly higher than that in other samples. The greater the CF supplementation (5%) the lower the syneresis on the 21st day of storage. The CF+PC (5%) sample was determined to be a better source of Ca, Mg, P and Fe than the Control and PC yoghurts. The sensory property of yoghurt involving PC decreased significantly with 5% CF. 2.5% CF+PC was the highest-scored sample.